Microhabitat use and multivariate pattern of motile epifaunal community in relation to sediment grain size in a tropical seagrass meadow (2008)
The relationship between habitat physical structure and motile epifauna community associated to a Seagrass bed dominated by Thalassia testudinum was study over the isobaths of 1 and 3 m, in terms of species diversity, organisms density, micro habitat use and multivariate species pattern in association with Seagrass biomass, shoot and leaf density, leaves long and wide, epiphytic and rizophytic algae biomass, sponges biomass and sediment grain size. Seagrass features showed significant differences between depths, instead epiphytic and rizophytic algae, sponges biomass and sediment grain size did not. Though differences exhibited by Seagrass, epifaunal species diversity and organism density neither were different between depths. In the same way none Seagrass feature showed strong correlations with faunal descriptors, tending even to be negative instead positive.